The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3386/w26751
|View full text |Cite
|
Sign up to set email alerts
|

Drug Firms' Payments and Physicians' Prescribing Behavior in Medicare Part D

Abstract: Meeting. Anup Das provided excellent research assistance. Colleen Carey acknowledges the financial support of the Robert Wood Johnson Foundation. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…We consider our approach to be appropriate for several reasons. First, as many researchers have noted, extensive margin effects of payments are large and the evidence on heterogeneity of effects by payment size is mixed (see, e.g., Carey et al (2017), Yeh et al (2016), and DeJong et al (2016)). We confirm this in our analyses in Section 3: cardiologists' tendency to prescribe firms' drugs is not increasing significantly in the dollar value of interactions.…”
Section: A Note On "Meals" and Cross-sectional Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider our approach to be appropriate for several reasons. First, as many researchers have noted, extensive margin effects of payments are large and the evidence on heterogeneity of effects by payment size is mixed (see, e.g., Carey et al (2017), Yeh et al (2016), and DeJong et al (2016)). We confirm this in our analyses in Section 3: cardiologists' tendency to prescribe firms' drugs is not increasing significantly in the dollar value of interactions.…”
Section: A Note On "Meals" and Cross-sectional Identificationmentioning
confidence: 99%
“…This places our study in contrast to Carey et al (2017), Datta and Dave (2016), Mizik and Jacobson (2004), in which the researchers include physician fixed effects to take out persistent unobserved differences across physicians. 32 The average treatment effect of a pharmaceutical firm providing one fewer meal to a physician in the context of a long physician-firm relationship, or of providing the first meal to a physician at the initiation of a physician-firm relationship, may be very different than the average treatment effect of turning an entire relationship on or off.…”
Section: A Note On "Meals" and Cross-sectional Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our paper contributes to a growing body of literature investigating the effect of pharmaceutical marketing on prescribing decisions (David et al 2010;DeJong et al 2016;Larkin et al 2017;Shapiro 2018a;Sinkinson and Starc 2018;Grennan et al 2018). Our empirical approach, which accounts for physician-drug fixed effects, is most similar to Carey et al (2015). Studying an earlier time period and a different set of drugs, Carey et al (2015) found that pharmaceutical payments increase the targeted doctor's prescribing volume.…”
Section: Introductionmentioning
confidence: 98%